Traditional and non-traditional behavioral tests demonstrate the attenuation of cognitive deficits by therapeutic hypothermia in a rat model of neonatal hypoxic–ischemic encephalopathy - Saadat, Angela; Kaszowski, Cortney; Pallera, Haree; Lattanzio, Frank; Britten, Richard A.; Sulaiman, Asna; Newman, Stephanie; Hosseini, Alireza; Shah, Tushar (Frontiers in Behavioral Neuroscience, 2025)
IntroductionNeonatal hypoxic-ischemic encephalopathy (HIE) is neurological disease caused by the deprivation of oxygen and blood flow to the brain during the developmentally-critical perinatal period. Therapeutic hypothermia (TH) is the standard of care treatment for HIE, though cognitive deficits can persistent throughout life despite treatment. The nature of these deficits, and the impacts of TH and sex are not well understood, and this presents a key barrier in the development of novel therapeutics.MethodsThe goal of this study was to enhance the characterization and measurement of cognitive outcomes with tasks that measure spontaneous behaviors in a rodent models of HIE. Mild-moderate HIE was induced in term-equivalent rats by Vannucci’s method and a subset of rats were treated with TH. Cognitive performance was assessed between 6-12 weeks of age.ResultsHyperactivity and topographical disorientation were observed in HIE rats. Injured rats also spent less time investigating a novel object, suggesting HIE reduced their ability to encode or recognize a familiar object and switch attention to a new object. In a food protection test, injured rats failed to detect an approaching robber rat and protect food items, an indication of impaired attention and egocentric spatial processing. TH treatment resulted in sex-specific attenuation of deficits in attention, learning and skill acquisition, feeding, and processing self-centered spatial cues.DiscussionThese observations highlight the need for deeper understanding of the enduring social and cognitive consequences of neonatal HIE including cases where therapeutic hypothermia was administered. This can pave the way for the development of tailored interventions that enhance the ability of HIE survivors to navigate the complex social and cognitive landscape of adult life.